Prevalence of Overweight and Obesity and Its Association with Nutrition-related Knowledge, Attitudes and Practices (KAP) Among Malaysian Deaf Adults - Yap, Anastasia Xin Wei; You, Yee Xing; Zaman, Farisah Najwa; Azlan, Ain Nasuha; Mohd Rashid, Syar Meeze; Krishnasamy, Shanthi; M Zapawi, Muhamad Mustaqim; Suzana, Suzana (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study examines the prevalence of overweight and obesity and determines the association between nutrition-related Knowledge, Attitudes, and Practices (KAP) and obesity among deaf adults from low-income households in Klang Valley, Malaysia. Using purposive sampling, 120 deaf adults from three community centres participated in this cross-sectional study. Anthropometric measurements and sociodemographic data were taken along with information on nutritionrelated KAP were collected via a validated questionnaire with assistance from a certified Malaysian sign language interpreter. The average age of participants was 43.1±10.5 years, with a majority being female, Malay, and educated at the secondary level. Overweight and obesity prevalence reached 58.3%. Mean scores for nutrition-related KAP were 53.1±17.5, 4.2±1.7, and 7.4±2.2, respectively. Lower scores in healthy eating practices were significantly associated with higher odds of obesity after adjusting for age, ethnicity, education years, waist-to-hip ratio and body fat percentage (OR=0.73; 95% CI: 0.55‒0.97; p<0.05). Poor eating practices are associated with obesity among deaf adults. A targeted nutrition education initiative addressing the specific needs of this population is essential to reduce obesity risks.